Peran Literasi Pajak dalam Meningkatkan Kepatuhan UMKM di Kota Baubau: Tinjauan terhadap Strategi Sosialisasi DJP Pasca Implementasi PP 55/2022 - Adan, Laode Muhammad Hasrul Adan; Rais, Muhammad; Wulandari, Wulandari; Akbarsyah, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Baubau City has a direct impact on their compliance in fulfilling tax obligations, especially after the implementation of Government Regulation Number 55 Year 2022. This research aims to improve the understanding of MSME taxation through socialization and tax literacy education activities designed in the form of collaborative-based community service. The methods used include initial surveys, socialization seminars, tax literacy classes, tax reporting simulations (e-filing and e-form), as well as FGDs and technical assistance. The results showed a significant increase in participants' understanding of tax obligations and their ability to conduct tax reporting independently. This community-based educational approach proved effective in shaping voluntary compliance behavior, in line with the theory of tax literacy and taxpayer compliance behavior. The implications of these results suggest that collaboration between universities and tax authorities can be a sustainable alternative strategy in improving tax awareness and compliance of the MSME sector